2015
DOI: 10.1071/rd13269
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of regulator of G-protein signalling 2 (Rgs2) leads to abnormal early mouse embryo development in vitro

Abstract: Regulator of G-protein signalling 2 (Rgs2) is involved in G-protein-mediated signalling by negatively regulating the activity of the G-protein α-subunit. In the present study, the expression patterns of Rgs2 in mouse ovarian tissues and early embryos were determined by semiquantitative reverse transcription-polymerase chain reaction, immunohistochemistry and immunofluorescent analyses. Rgs2 expression was observed in the ovarian tissues of adult female mice, with an almost equal expression levels during differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Steroid hormones produced in the ovaries, such as estrogen and progesterone, play (Das et al, 2009(Das et al, , 2012Paria, Tan, Lubahn, Dey, & Das, 1999). We found that RGS2 is periodically expressed in murine ovarian tissue in time with the estrous cycle, in response to the release of ovarian hormones (Zhu et al, 2015). .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Steroid hormones produced in the ovaries, such as estrogen and progesterone, play (Das et al, 2009(Das et al, , 2012Paria, Tan, Lubahn, Dey, & Das, 1999). We found that RGS2 is periodically expressed in murine ovarian tissue in time with the estrous cycle, in response to the release of ovarian hormones (Zhu et al, 2015). .…”
Section: Discussionmentioning
confidence: 77%
“…Steroid hormones produced in the ovaries, such as estrogen and progesterone, play very important roles in female reproduction, such as promoting the follicular development (Mendoza et al, ), releasing mature oocytes (Morrison, Waggoner, Whitworth‐Langley, & Stith, ; Salehnia & Zavareh, ), and regulating the proliferation and differentiation of uterine cells (Das et al, , ; Paria, Tan, Lubahn, Dey, & Das, ). We found that RGS2 is periodically expressed in murine ovarian tissue in time with the estrous cycle, in response to the release of ovarian hormones (Zhu et al, ). .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, expression of Rgs2 , a negative regulator of Gα, has been reported in early embryos from the zygote to the blastocyst (Zhu et al, ). Reduced levels of Rgs2 expression led to abnormal embryonic development in vitro, with embryos arrested at the two‐ or four‐cell stage, and a significant decrease in the expression of zygotic activation‐related genes.…”
Section: G Protein‐coupled Receptors (Gpcrs)mentioning
confidence: 99%
“…Several genes such as MuERV-L, Zscan4d, Hsp70.1 and eIF1A are regarded as "marker" genes in studies assessing ZGA status [42,[48][49][50][51][52][53]. To investigate whether the observed two-cell blockage correlated with ZGA, alterations in the expression of these ZGA markers in two-cell embryos after Trps1-siRNA were examined.…”
Section: Knockdown Of Trps1 Elevated the Expression Levels Of Zscan4dmentioning
confidence: 99%